Coconut Pulp as a Learning Media to Stimulate The Creativity Of Early Children - Henny, Henny; Ahmad, Wa Ode Febrianti (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2025)
This research investigates how coconut pulp can be an innovative learning tool to nurture creativity in young learners at Lahumoko Kindergarten, Indonesia. We observed children's creative expression blossom excitingly through hands-on activities like free drawing, collage creation, color mixing experiments, and letter writing with coconut pulp. The study, conducted using participatory action research, revealed that this natural material sparked imagination and strengthened preschoolers' fine motor abilities and teamwork. While most children thrived, we noticed some needed extra guidance to move beyond copying peers - reminding us how skilled teacher support can make all the difference. These findings emphasize why educators need training to effectively lead open-ended, play-based activities. Coconut pulp's success as a learning tool shows how everyday materials from children's environments can transform education when used creatively. This approach aligns with established educational theories while offering practical, sustainable solutions for early childhood classrooms. Most importantly, it demonstrates how simple resources can unlock young minds' potential with thoughtful teaching strategies.